Resistin Is Increased in Periodontal Cells and Tissues: In Vitro and in Vivo Studies - Nogueira, Andressa V. B.; Nokhbehsaim, Marjan; Tekin, Sema; De Molon, Rafael S. [UNESP]; Spolidorio, Luis C. [UNESP]; Memmert, Svenja; Damanaki, Anna; Jäger, Andreas; Eick, Sigrun; Deschner, James; Cirelli, Joni A. [UNESP] (Hindawi, 2020)
Resistin, a proinflammatory adipokine, is elevated in many inflammatory diseases. However, little is known about its performance in periodontitis. The present study is aimed at evaluating resistin expression and synthesis in periodontal cells and tissues under inflammatory/microbial stress in addition to its effects on the periodontium. In vivo, 24 male rats were randomly divided into two groups: control and ligature-induced periodontal disease. After 6 and 12 days, animals were sacrificed to analyze gene expression of adipokines, bone loss, inflammation, and resistin synthesis. In vitro, human periodontal ligament (PDL) fibroblasts were used to evaluate the expression of resistin after inflammatory stimuli. In addition, PDL fibroblasts were exposed to resistin to evaluate its role on soft and hard tissue metabolism markers. The periodontitis group demonstrated significant bone loss, an increase in the number of inflammatory cells and vascular structures, an increase in resistin expression and synthesis, and a decrease in the expression of adiponectin, leptin, and its functional receptor. PDL fibroblasts showed a significant increase in resistin expression and synthesis in response to the inflammatory stimulus by IL-1β. Resistin induced an increase in cytokine expression and a decrease in the regulation of some hard tissue and matrix formation genes in PDL fibroblasts. These data indicate that resistin is produced by periodontal cells and tissues, and this effect is enhanced by inflammatory stimuli. Moreover, resistin seems to interfere with soft and hard tissue metabolism during periodontitis by reducing markers related to matrix formation and bone tissue.